BROWN, Wendy. Undoing the Demos: Neoliberalism's Stealth Revolution. New York: Zone Books, 2015. - Alexandre Marinho Pimenta (Política & Sociedade)
Resenha do Livro: BROWN, Wendy. Undoing the Demos: Neoliberalism's Stealth Revolution. New York: Zone Books, 2015.